The role of copper decorating poly(1,8-diaminonaphthalene)/graphene electrodes as a catalyst in the determination of nitrite - Hong Van, Bui Thi; Thuy, Do Thi; Huy, Nguyen Le; Mai, Nguyen Thi Tuyet; Lam, Tran Dai; Dung, Nguyen Tuan (Vietnam Journal of Science and Technology, 2022)
. Electroactive poly(1,8-diaminonaphthalene) is known to have a high affinity for metal ions thanks to amine and imine groups in the polymer chain. However, electrochemical sensors based on pristine P(1,8-DAN) have a major drawback concerning its poor electrical conductivity. To solve this problem, recently P(1,8-DAN) has been modified with some advanced nanomaterials such as carbonaceous materials or different metallic elements. In this research, we reported the synthesis and electrochemical characterization of a poly(1,8-diaminonaphthalene)/graphene composite film capable of adsorbing Cu2+ ions towards the application of nitrite sensing. P(1,8-DAN) was directly electropolymerized on graphene-coated glassy carbon electrode by a potential cycling between –0.15 and +0.95 V (vs. SCE) at a scan rate of 0.05 V/s, in aqueous solution containing 1.0 M HClO4 and 1.0 mM monomer 1,8-DAN,. The adsorption of Cu2+ ions onto the P(1,8-DAN) thin film was caried out in 0.1 M Cu(NO3)2 solution at 80 oC, followed by electrochemically redution to metal Cu0 by applying -0.4 V. The obtained copper decorating poly(1,8-diaminonaphthalene)/graphene (Gr/P(1,8-DAN)-Cu) electrodes acted as a catalyst in the enhancement of electrochemical signal for the determination of nitrite. The linear voltammetric response to the nitrite concentration was observed by a square wave voltammetric technique in the range of 0.69 to 1.12 mM with a detection limit of 0.13 mM. The results open up the path for designing other nitrite sensing based on our novel approach.